VIII. ATTACHMENT AND SLEEP AMONG TODDLERS: DISENTANGLING ATTACHMENT SECURITY AND DEPENDENCY. Issue 1 (March 2015) - Bélanger, Marie‐Ève; Bernier, Annie; Simard, Valérie; Bordeleau, Stéphanie; Carrier, Julie
ABSTRACT: Many scholars have proposed that parent‐child attachment security should favor child sleep. Research has yet, however, to provide convincing support for this hypothesis. The current study used objective measures of sleep and attachment to assess the longitudinal links between mother‐child attachment security and subsequent sleep, controlling for child dependency. Sixty‐two middle‐class families (30 girls) were met twice, when children were 15 months (Wave 1; W1) and 2 years of age (Wave 2; W2). At W1, mother‐child attachment was assessed with the observer version of the Attachment Q‐Sort. At W2, children wore an actigraph monitor for 72 hr. Results indicated that children more securely attached to their mothers subsequently slept more at night and had higher sleep efficiency, and these predictions were not confounded by child dependency. These findings suggest a unique role for secure attachment relationships in the development of young children's sleep regulation, while addressing methodological issues that have long precluded consensus in this literature.